Матричная дифференциально-алгебраическая краевая задача с импульсным воздействием - Чуйко, С.М.; Дзюба, М.В. (Нелінійні коливання, 2017)
Знайдено необхiднi та достатнi умови iснування, а також конструкцiю узагальненого оператора Грiна для побудови розв’язкiв лiнiйної матричної диференцiально-алгебраїчної крайової задачi з iмпульсною дiєю. Для розв’язання матричної диференцiально-алгебраїчної крайової задачi з iмпульсною дiєю використано оригiнальнi умови розв’язностi, а також конструкцiю загального розв’язку лiнiйного матричного рiвняння. We find necessary and sufficient conditions for existence of solutions of a linear matrix boundary-value problem for a system of matrix differential-algebraic equations with impulsive effect. We also construct a generalized Green’s operator of linear boundary conditions for a system of matrix differential-algebraic equations with impulsive effect. To solve the matrix differential-algebraic boundary problem with impulsive effect, we use original solvability conditions and the structure of the general solution of the linear matrix equation.